PENGARUH PERSEPSI HARGA LOKASI DAN KUALITAS PELAYANAN TERHADAP MINAT BELI PADA TOKO MEGA KOMPUTER KOTA BENGKULU - Onsardi Onsardi; Fitri Wulansari (Yayasan Insani Mandiri Santani, 2022)
The purpose of this study was to determine the effect of location price perception and service quality on buying interest at the Bengkulu City Mega Computer Store to determine the most dominant factor influencing buying interest. This study uses survey research methods with quantitative data analysis. The population used in this research is the consumer of the Bengkulu city mega computer shop whose number is unknown (infinite) and the sampling in this study is accidental sampling technique. Based on the results of multiple regression, the regression equation Y = 1.323 + 0.607 (X1) + 0.344 (X2) +0.142 (X3) is obtained. The results and the hypothesis show that the price shows a value of > (9.200 > 1.973) and (sig a = 0.000 < 0.050). The location shows the value > (7.163 > 1.973) and (sig a = 0.000 < 0.050). Service quality shows the value > (2.227 > 1.973) and (sig a = 0.027 < 0.050). Simultaneously (F) Price, Location and Quality of Service have a significant effect on buying interest. Partially (t) the three variables Price, location and service quality have a significant influence on buying interest. Keywords: Price, Location, Quality of Service, Buying Interest